Pattern recognition Joint 34th DAGM and 36th OAGM Symposium, Graz, Austria, August 28-31, 2012.proceedings - Pinz, Axel (Lecture notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 34th Symposium of the German Association for Pattern Recognition, DAGM 2012, and the 36th Symposium of the Austrian Association for Pattern Recognition, OAGM 2012, held in Graz, Austria, in August 2012. The 27 revised full papers and 23 revised poster papers were carefully reviewed and selected from 98 submissions. The papers are organized in topical sections on segmentation, low-level vision, 3D reconstruction, recognition, applications, learning, and features.